An exploration of the use of vernacular architecture by boutique hotels : a comparative study of Singapore, Malacca and Penang. - Kwek, Benjamin Xu Yuan. (2012)
Boutique hotels in vernacular architecture have attracted limited academic interest. This study focuses on the use of such architecture by boutique hotels, and serves as a comparative study of Singapore, Malacca and Penang. An extensive literature review was done to lay the context of the study. Findings were then achieved through a series of site investigations, secondary data analysis and in-depth interviews. Findings highlighted the role of the government’s involvement and the extent of heritage preservation at these hotels. Further included, are insights from the hotel owners themselves, which showcase the business acumen behind their decisions for opening such accommodation, as well as the reasons behind customer choice. The hotelier’s awareness of legislation affecting the extent of preservation and the consciousness of commercial viability within the constraints of a heritage building are important practical implications that must be considered prior to opening.